Phonological Development of Children With Speech Delay - Yana Shanti Manipuspika (Program Studi Magister Ilmu Linguistik Universitas Warmadewa, 2019)
A case research is a valuable means of providing information about the outcomes of speech and language intervention. The present research aims at documenting phonological development of three subjects who were enrolled in a therapy. This descriptive, cross-sectional research aimed to document the phonological development of speech delayed children whose ages are between 2-4 years. The focus is also to determine the causes and treatment of children with speech delay. The results showed significant changes in two of the subjects’ speech production-the two-year-old H displayed an ability to produce imitative sounds and non-imitative ones; meanwhile, the four-year-old AK also performed perfect imitative sounds, yet she cannot produce nasalized coda. The three-year-old AR, however, could not produce meaningful speech. Evaluation revealed development of the three subjects were affected by the exposure to language at home. A younger age child performed better during the therapy sessions compare to the one in older age whose delay might be caused by early neglect. Speech therapy emphasized on the importance of imitation through a modeling activity in the session, so that the children could imitate the sound first while providing context through pictures.